Impact of Aortic Arch Anatomy on Technical Performance and Clinical Outcomes in Patients with Acute Ischemic Stroke - Knox, J A; Alexander, M D; McCoy, D B; Murph, D C; Hinckley, P J; Ch'ang, J C; Dowd, C F; Halbach, V V; Higashida, R T; Amans, M R; Hetts, S W; Cooke, D L (American journal of neuroradiology : AJNR, 2020)
Arterial access is a technical consideration of mechanical thrombectomy that may affect procedural time, but few studies exist detailing the relationship of anatomy to procedural times and patient outcomes. We sought to investigate the respective impact of aortic arch and carotid artery anatomy on endovascular procedural times in patients with large-vessel occlusion. We retrospectively reviewed imaging and medical records of 207 patients from 2 academic institutions who underwent mechanical thrombectomy for anterior circulation large-vessel occlusion from January 2015 to July 2018. Preintervention CTAs were assessed to measure features of the aortic arch and ipsilateral great vessel anatomy. These included the cranial-to-caudal distance from the origin of the innominate artery to the top of the aortic arch and the takeoff angle of the respective great vessel from the arch. mRS scores were calculated from rehabilitation and other outpatient documentation. We performed bootstrap, stepwise regressions to model groin puncture to reperfusion time and binary mRS outcomes (good outcome, mRS ≤ 2). From our linear regression for groin puncture to reperfusion time, we found a significant association of the great vessel takeoff angle ( = .002) and caudal distance from the origin of the innominate artery to the top of the aortic arch ( = .05). Regression analysis for the binary mRS revealed a significant association with groin puncture to reperfusion time ( < .001). These results demonstrate that patients with larger takeoff angles and extreme aortic arches have an association with longer procedural times as approached from transfemoral access routes.